2021
DOI: 10.1111/joor.13150
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of temporomandibular disorders in musicians: A systematic review and meta‐analysis

Abstract: Objective To determine the prevalence of temporomandibular disorders (TMD) in musicians. Materials and methods Electronic database searches and a manual search were performed. Qualitative and quantitative analysis including risk of bias was performed for studies that met the inclusion criteria. A meta‐analysis of proportions with a random effects model was performed, and heterogeneity was explored according to the moderating variable through subgroup analysis and metaregression. The certainty of the evidence w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Thus, the next step was to understand how OFP symptoms fluctuate with the musical performances and distinctive practices of each musician group. For this purpose, we used face validity questionnaires adopted by previous surveys [ 12 , 13 , 15 , 16 ]. Interestingly, while exploring the presence of OFP while performing or playing music ( Table 5 ), we found that it was significantly higher (more than two-fold) in the two instrumentalist groups when compared to vocalists (41.4–48% vs. 17.2%, p = 0.002).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the next step was to understand how OFP symptoms fluctuate with the musical performances and distinctive practices of each musician group. For this purpose, we used face validity questionnaires adopted by previous surveys [ 12 , 13 , 15 , 16 ]. Interestingly, while exploring the presence of OFP while performing or playing music ( Table 5 ), we found that it was significantly higher (more than two-fold) in the two instrumentalist groups when compared to vocalists (41.4–48% vs. 17.2%, p = 0.002).…”
Section: Resultsmentioning
confidence: 99%
“…A general information questionnaire collected the demographic data, and the following questions were added to assess musical practice confounders according to previous systematic studies and surveys [ 12 , 13 , 15 , 16 ]: 1. instrument(s) most often used/played? ; 2. total number of years of practice?…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of TMD is also related to occupation. The overall combined prevalence of TMD among musicians is about 53.9% [ 20 ]. The main symptoms of TMD include muscle and joint-related pain, decreased jaw movement, headache, tinnitus [ 21 ], stiffness, fatigue, and other potentially related symptoms [ 22 ].…”
Section: Discussionmentioning
confidence: 99%